2012
DOI: 10.1007/s10856-012-4568-8
|View full text |Cite
|
Sign up to set email alerts
|

Random amphiphilic copolymeric sub-micro particles as a carrier shielding from enzymatic attack for peptides and proteins delivery

Abstract: The development of peptide drugs and therapeutic proteins is limited by their rapid clearance in liver and other body tissues by proteolytic enzymes, and consequently peptides and proteins are difficult to administer except by injection. There is a growing effort to circumvent these problems by designing strategies to deliver these drugs to specific site of the body. Among them, this peptide carrier presents several advantages for protein therapy including stability in physiological buffer and lack of toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Stimuli-responsive polymer nanoparticles have drawn increasing interests in drug delivery due to their various advantages. These polymer nanoparticles could trigger drug release in response to local environmental conditions such as pH, temperature, light, ionic strength, magnetic field and glucose. Among these stimuli, a most important one is glucose molecule, because insulin-dependent diabetes mellitus characterized by accumulating glucose concentrations in the blood has been a major global public health epidemic. , Moreover, the current treatment for diabetes requires persistent monitoring of blood glucose levels and multiple daily insulin injections . This injection not only impinges on the patient quality of life but also fails to precisely control the insulin dosage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimuli-responsive polymer nanoparticles have drawn increasing interests in drug delivery due to their various advantages. These polymer nanoparticles could trigger drug release in response to local environmental conditions such as pH, temperature, light, ionic strength, magnetic field and glucose. Among these stimuli, a most important one is glucose molecule, because insulin-dependent diabetes mellitus characterized by accumulating glucose concentrations in the blood has been a major global public health epidemic. , Moreover, the current treatment for diabetes requires persistent monitoring of blood glucose levels and multiple daily insulin injections . This injection not only impinges on the patient quality of life but also fails to precisely control the insulin dosage.…”
Section: Introductionmentioning
confidence: 99%
“…Jennifer et al developed poly­(3-acrylamidophenylboronic acid pinacol ester)- b -poly­( N , N -dimethylacrylamide) and studied the sugar- and pH-responsive behaviors . Previously, our group has established phenylboronic acid-based block glycopolymer and explored their potential as glucose-responsive vehicles in drug delivery. Although block polymers play an important role in these copolymers, it should be noted that random copolymer with the similar polymeric configuration exhibited good stimuli-response behaviors. Tian et al prepared amphiphilic random copolymer that showed photoresponse behavior . Chi et al displayed a novel thermo- and photoresponsive polypseudorotaxane between pillararene WP7 and an azobenzene-containing random copolymer .…”
Section: Introductionmentioning
confidence: 99%
“…Aliquots of 200 µl were withdrawn at scheduled time intervals (15/30/60/120 min) and the reaction was promptly halted by adding 100 µl 0.1 N hydrochloric acid solution. After the mixture was subjected to centrifugation (14,000 rpm, 30 min), the leftover insulin content in the supernatant was determined using HPLC method [16] .…”
Section: Methodsmentioning
confidence: 99%